Popularisation of mathematics (Pempopularan Matematik) - Abdul Razak Salleh (Penerbit Universiti Kebangsaan Malaysia, 2011)
Mathematics is generally regarded as the most dry subject at school, made up of routine,difficult, boring, arcane and irrelevant calculations which have nothing to do with discovery and imagination. You may have noticed how terms in mathematics have an unnerving effect on most students as well as the public. “Dull” and “Urgh” are the most common epithets often used to describe the subject. Whether we realise it or not, mathematics is around us, in our everyday life, and we are using the subject. Mathematics exists in nature. Mathematics is used in the kitchen; when we do our shopping, build a house, travel on the highway, and in whatever things that we do. Even then, whenever we talk about mathematics, many fear the subject; they have the mathematicophobia, and try to avoid the subject. The fact is that,mathematics is a part of our life. We have to make the public aware of this. This is the duty of mathematicians or mathematical scientists. Popularisation of mathematics could be done at various levels in the society, young and old, and wherever we are; at home, nurseries, schools,universities, offices, supermarkets, and on the highways. In this paper we will discuss how this could be achieved.